Pelatihan Pemetaan Topografi Menggunakan Waterpas dan Teodolit bagi Siswa SMK Budi Bangsa Luwu Utara Provinsi Sulawesi Selatan - Agus Ardianto Budiman; Nurliah Jafar; Firdaus Firdaus; Abdul Salam Munir; Rahayu Achmad (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
To ensure the quality of education in vocational schools (Sekolah Menengah Kejuruan or SMK), the government intervenes through the Skills Competency Test (Uji Kompetensi Keahlian or UKK). During the UKK process for SMK Budi Bangsa students in March 2018, it was found that the participants generally had not yet mastered the material to be tested, specifically the use of topographic mapping equipment. This is likely due to the insufficient availability of adequate facilities and infrastructure at SMK Budi Bangsa. Therefore, training on the use of topographic mapping equipment is necessary to better prepare SMK Budi Bangsa students for a similar exam the following year. The topographic mapping training, using auto level and theodolite tools, aims to enhance students' knowledge and skills in accordance with the equipment usage guidelines and refer to the Code 1556 Vocational Practice Exam Assessment Sheet. The topographic mapping training was conducted at SMK Budi Bangsa from January 29 to February 4, 2019. The method used involved theoretical presentations on topographic mapping in general and the specific use of auto level and theodolite tools, as well as practical exercises on the usage of these tools, measurement and data processing, and the creation of topographic maps. The training activities were attended by 27 students, consisting of 14 students from class X, 3 students from class XI, and 10 students from class XII. From only 7.4% of the participants who initially possessed the knowledge and skills according to the first two stages of the reference before the training, they achieved improvement, with all participants acquiring the knowledge and skills according to all stages of the planned reference.